Analisis Kepatuhan Hukum Bank terhadap Regulasi OJK dan BI dalam Implementasi Layanan Digital Banking - Rozikin, Muhammad (Journal of Islamic Finance and Syariah Banking, 2025)
This study aims to analyze the level of legal compliance of banks with regulations established by the Financial Services Authority (OJK) and Bank Indonesia (BI) in the provision of digital banking services in Indonesia. The research focuses on the extent to which banking institutions are able to implement the principles of prudence, good governance, and compliance with legal provisions amidst the rapid development of financial technology. The research method used is a descriptive qualitative approach with literature study techniques through a review of laws and regulations, academic literature, and previous research results relevant to the topic of legal compliance and digital banking regulations. The analysis was conducted to understand the relationship between regulations, financial institutions' compliance behavior, and their impact on the stability of the national banking system. The results show that the level of legal compliance of banks is significantly influenced by the effectiveness of regulations, legal awareness of industry players, and institutional capacity in implementing internal supervisory systems. The OJK and BI have a strategic role in regulating, supervising, and adapting regulations to align with the development of digital banking, including through the implementation of digital-based supervisory technology (RegTech). Legal compliance is a crucial element in maintaining public trust, transaction security, and the sustainability of digital banking in Indonesia.